Chemistry and Medicines: An Introductory Text - James Ralph Hanson (RSC Publishing, 2006)
Medicinal chemistry incorporates bio-organic chemistry, organic synthetic methods, physical organic chemistry and organic reaction mechanisms. These areas of chemistry are crucial to the design and synthesis of new drugs, both in academia and the pharmaceutical industry. Chemistry and Medicines: An Introductory Text provides a general introduction to this fascinating subject. The first chapters contain a brief historical introduction followed by a description of the chemical features involved in the adsorption, distribution, metabolism and excretion of a drug. The remaining chapters describe the chemistry underlying the design and synthesis of some of the key drugs used to combat some major diseases of the peripheral and central nervous system, infectious diseases and cancers. A glossary and suggestions for further reading complete this textbook. The book is aimed at those studying advanced undergraduate and postgraduate courses in medicinal chemistry